The American paradox : spiritual hunger in an age of plenty - Myers, David G. (Yale University Press, 2000)
For Americans entering the twenty-first century, it is the best of times and the worst of times. Material wealth is at record levels, yet disturbing social problems reflect a deep spiritual poverty. In this compelling book, well-known social psychologist David G. Myers asks how this paradox has come to be and, more importantly, how to spark social renewal and dream a new American dream. Myers explores the research on social ills from the 1960s through the 1990s and concludes that the materialism and radical individualism of this period have cost us dearly, imperiling our children, corroding general civility, and diminishing our happiness. However, in the voices of public figures and ordinary citizens he now hears a spirit of optimism. The national dialogue is shifting away from the expansion of personal rights and towards enhancement of communal civility, away from efforts to raise self-esteem and towards attempts to arouse social responsibility, away from "whose values?" and towards "our values". Myers analyses in detail the research on educational and other programmes that deal with social problems, explaining which seem to work and why. He then offers positive and well-reasoned advice, suggesting that a renewed social ecology for America will rest on policies that balance "me thinking" with "we thinking."